The role of sex in particle‐induced inflammation and injury. (30th September 2019) - Ray, Jessica L.; Fletcher, Paige; Burmeister, Rachel; Holian, Andrij
Abstract: The use of engineered nanomaterials within various applications such as medicine, electronics, and cosmetics has been steadily increasing; therefore, the rate of occupational and environmental exposures has also increased. Inhalation is an important route of exposure to nanomaterials and has been shown to cause various respiratory diseases in animal models. Human lung disease frequently presents with a sex/gender‐bias in prevalence or severity, but investigation of potential sex‐differences in the adverse health outcomes associated with nanoparticle inhalation is greatly lacking. Only 20% of basic research in the general sciences use both male and female animals and a substantial percentage of these do not address differences between sexes within their analyses. This has prevented researchers from fully understanding the impact of sex‐based variables on health and disease, particularly the pathologies resulting from the inhalation of particles. The mechanisms responsible for sex‐differences in respiratory disease remain unclear, but could be related to a number of variables including sex‐differences in hormone signaling, lung physiology, or respiratory immune function. By incorporating sex‐based analysis into respiratory nanotoxicology and utilizing human data from other relevant particles (e.g., asbestos, silica, particulate matter), we can improve our understanding of sex as a biological variable in nanoparticle exposures. This article is categorized under: Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials Abstract : Sex‐differences in local and systemic outcomes following particle inhalation